Análise experimental de lajes lisas unidirecionais de concreto armado ao puncionamento simétrico ou assimétrico - FERREIRA, Maurício de Pina (2006)
Punching is normally a critical case in the design of reinforced concrete flat slabs. According to many design codes, punching develops in a more unfavorable way in cases where the load is asymmetrically applied, due to unbalanced bending moments at slab-column connections. In order to evaluate the normative prescriptions in these cases, 12 reinforced concrete oneway flat slabs ( c f ' between 36 and 58 MPa) were submitted to symmetric or asymmetric punching. The slabs dimensions were (1.800 x 1.800 x 110) mm with the load being applied through a metallic plate simulating a square column with (85 x 85 x 50) mm. This research had as variables, in addiction to the load position, the reinforcement rate in transversal direction, in order to evaluate their influence in the punching ultimate resistance of one-way slabs. Results for vertical deflections, concrete surface and flexural reinforcement strains, cracking pattern, observed ultimate loads and failure modes are presented and analyzed. Also were analyzed the estimates of 6 design codes, with 3 European and 1 North-American, beyond the versions from 1978 and 2003 of the Brazilian structural concrete design code. A numerical analysis using the Finite Elements Method to simulate the slabs behavior is presented and its results are compared to the experimentally observed ones. The results showed that, unlike the normative previsions, punching resistance doesnt reduce linearly with the increments in the loads eccentricities, with the flexural effects significantly influencing the ultimate punching resistance. Even in one-way slabs, the transversal reinforcement rate showed significant influence on the slabs force distribution, interfering in the punching resistance.